Analysis, design and simulation of RC passive damping network in a simple distributed DC power system using PSPICE - Jusoh, Awang; Salam, Zainal; Lim, Aik Jin (Faculty of Electrical Engineering, 2007)

(untitled)
The sub-system interaction and instability phenomena are a common problem in the Distributed Power System (DPS). In order to regulate the output voltage or the speed, the internal control function of a converter known as constant power load (CPL) results in the converter tends to draw a constant power. This phenomenon cause the input impedance of CPL has negative incremental input impedance, which tends to create instability as it is connected to a system. This paper concerns about the compensation method used to improve the stability of two or more connected subsystems, consisting of an L-C filter and a CPL. A compensation method known as passive damping network containing only RC components is examined purposely to eliminate and reduce the instability of the subsystem. The passive damping network was designed and simulated using PSpice. The results show that the designed passive damping network is suitable for small-scale power distribution system that contains constant power load with power level of 1 kW.